Mechanical tests of highly porous heat-protecting composite material - et. al., O.S. Tarasenko, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The paper considers the experimental problem of determining the physical and mechanical properties and stress-strain state of plates made of heat-shielding highly porous fibrous materials made of quartz fibers and differing in their structural structure (and, accordingly, in the properties of thermal conductivity, rigidity, strength). The modulus of elasticity and ultimate strength of the samples cut from the heat-shielding plate are determined, stress-strain diagrams are constructed.